Sustainable architecture and earthquake resilience of vernacular Zegalli houses in northern Iran - Zaryoun, Mona; Hosseini, Mahmood; Soleymani, Kaveh (Emerald Group Publishing Ltd, 2022)
Purpose The main purpose of this study is revival of vernacular architecture of Zegalli houses, which can be beneficial in several aspects of sustainable architecture, and therefore, its reuse in contemporary architecture can be strongly recommended. Zegalli houses, in northern Iran, are almost-entirely wooden vernacular houses, which beside to having several aspects of sustainable architecture, have shown good resistance against past earthquakes. Their relatively good seismic performance is mainly because of their specific timber foundation, which creates a kind of rocking/rolling isolation, as well as their light weight and diagonally braced stiff walls. Design/methodology/approach In this paper, first the architectural features of Zegalli houses, particularly energy efficiency, sustainability and eco-friendliness are described. Then, their structural system, focusing more on their foundation, is discussed. Finally, a simplified model of the house, developed in a powerful finite element analysis program, is introduced, and sample results of a series of time history analyses (THA), employing three-component accelerograms of three selected earthquakes, are presented. Findings Results of THA show that the rocking/rolling behavior of foundation timbers in various levels significantly reduces seismic response of the house, leading to its stability against earthquakes with peak ground acceleration up to 0.25 g. Practical implications Regarding the architectural and structural merits of Zegalli houses, they can be considered as sustainable vernacular architecture, and therefore, architects and civil and structural engineers are encouraged to reconsider the use of these houses, with some modifications, in future developments. Originality/value 3D dynamics analysis of Shikilli foundations of Zegalli houses is done for the first time in this study.
Keywords: Zegalli houses; Shikilli foundation; Vernacular architecture; Sustainability; Rocking and rolling isolation; Time history analysis; Finite element analysis